2022
DOI: 10.3390/insects13060517
|View full text |Cite
|
Sign up to set email alerts
|

Promising Insecticidal Efficiency of Essential Oils Isolated from Four Cultivated Eucalyptus Species in Iran against the Lesser Grain Borer, Rhyzopertha dominica (F.)

Abstract: The lesser grain borer, Rhyzopertha dominica (F.), causes damage to stored grains resulting in both quantitative and qualitative losses. The use of synthetic fumigants in the management of stored-product pests resulted in undesirable side effects such as environmental contamination and threat to human and animal health. In this study, the lethal and sublethal effects of essential oils from four Eucalyptus species, E. microtheca, E. procera, E. spatulata, and E. torquata were studied against R. dominica adults.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Consistent with our findings, CarE activity was significantly increased in Helicoverpa armigera (Hübner, 1808) larvae after exposure to quercetin ( Chen et al., 2017 ). Adult Rhyzopertha dominica (Fabricius, 1792) ( R. dominica) given with a sublethal dosage of eucalyptus essential oils showed increased α- and β-esterase activity ( Ebadollahi et al., 2022b ). The α- and β-esterase activity of adult R. dominica treated with lethal and sublethal doses of thymus essential oils was elevated, which is consistent with our results ( Ebadollahi et al., 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, CarE activity was significantly increased in Helicoverpa armigera (Hübner, 1808) larvae after exposure to quercetin ( Chen et al., 2017 ). Adult Rhyzopertha dominica (Fabricius, 1792) ( R. dominica) given with a sublethal dosage of eucalyptus essential oils showed increased α- and β-esterase activity ( Ebadollahi et al., 2022b ). The α- and β-esterase activity of adult R. dominica treated with lethal and sublethal doses of thymus essential oils was elevated, which is consistent with our results ( Ebadollahi et al., 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, sublethal biochemical disruption has been shown in treated insects, including the reduction of energy content resulting from the significant decrease of the protein and glycogen contents. In other hand, an inhibition of digestive amylase and protease enzyme activities, also, a significant decreases in the relative growth rate of insects (Ebadollahi et al, 2022) which confirm that E. torquata extract and essential oils can be used to control insect pests. Also, it found that possess acaricidal properties as reported by Ebadollahi et al (2017) which demonstrated that E. torquata leaves essential oils have strong toxicity against the adult females of Tetranychus urticae Koch and the observed LC50 values in the fumigation test was 3.59 μL/L air after 24 h.…”
Section: E Torquata As Pesticidementioning
confidence: 62%
“…It recommends planting E. torquata in protected areas as an ornamental tree in the public and private gardens due to its beautiful flowers and its medium size (El-Juhany and Al Al-Shaikh, 2015). The researchers were also exploring the potency of E. torquata by valuing their extracts and essential oils which show different biological activities such as antibacterial, antifungal (Ashour, 2008), cytotoxic (Ashour, 2008;Bardaweel et al, 2014;Lahmadi et al, 2021) and pesticidal activity (Ebadollahi et al, 2017;El Finti et al, 2022;Ebadollahi et al, 2022). Also, E. torquata considered an important sources of nectar and pollen for honeybees as showing an abundant flowering of long period and good quality of pollen and nectar for the nutrition of bee; for these reasons, it is frequently planted in arid regions (Eisikowitch et al, 2012;Saadaoui et al,2022 ).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…Regarding insect detoxification, metabolic systems are the key mechanisms for developing insecticide resistance [ 37 ]. Insect cytochrome P450 enzymes are present in organisms and are widely implicated in the detoxification of xenobiotics.…”
Section: Discussionmentioning
confidence: 99%